Complicit fictions : the subject in the modern Japanese prose narrative - Fujii, James A. (Berkeley : University of California Press, 1993)
In Complicit Fictions, James Fujii challenges traditional approaches to the study of Japanese narratives and Japanese culture in general. He employs current Western literary-critical theory to reveal the social and political contest inherent in modern Japanese literature and also confronts recent breakthroughs in literary studies coming out of Japan. The result is a major work that explicitly questions the eurocentric dimensions of our conception of modernity.
Narrating Resentment through Urban-Rural Tension: Shimazaki Toson's Kyushujin -- Changing Metaphors: From Vertical Hierarchy to Centralization in Toson't Hakai -- Between Stye and Language: the Meiji Sublect and Natsume Soseki's Neko -- Death, Empire, and the Search for History in Natsume Soseki's Kokoro -- Claiming the Urban Landscape: Tokuda Shusei as Discursive Creation -- From Sericulture to Piece-work: Visualizing the "Rowdy" Subject in Shusei's Arakure -- Epilogue: the Kindai Shosetsu and Origuchi Shinobu.
Includes bibliographical references (pages 257-266) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Japanese fiction -- 1868- -- History and criticism; Roman japonais -- 1868- -- Histoire et critique; LITERARY CRITICISM -- Asian -- General; Japanese fiction; Japanisch; Prosa; Subjekt; Subjectiviteit; Romans; Japans; Japanisch; Since 1868; Criticism, interpretation, etc